Are Islamic Equity Markets “Safe Havens”? Exploring the Contagion Effects Between Metal Future Markets and Malaysian Islamic Bonds Using DCC-FIGARCH During the Recent Global Financial Crisis of 2008 - Tsiaras, Konstantinos (International Journal of Economics, Management and Accounting, 2021)
This paper examines the time-varying conditional correlations between seventeen metal future markets and Malaysian Islamic bonds. We apply twelve sixvariate dynamic conditional correlation (DCC) FIGARCH models in order to capture potential contagion effects between the markets for the period 2007-2011. Empirical results reveal contagion during the under investigation period regarding the twelve sixvariate models, showing potential volatility transmission channels among the markets and implying that the sukuk bonds are not a safe haven during bearish times without portfolio diversification strategies. Findings have crucial implications for policymakers who provide regulations for the above derivative markets and for investors who invest long-term in Islamic bonds.